2013
DOI: 10.1161/strokeaha.112.679092
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Prevent Hydrocephalus After Severe Intraventricular Hemorrhage

Abstract: I ntraventricular hemorrhage (IVH) is a serious complication of preterm birth, and the number of infants at high risk for developing IVH is increasing as a result of the rise in the absolute number and improved survival of very premature infants with recent advances in neonatal intensive care medicine. 1,2 Over half of infants with severe IVH (grade ≥3) die or develop posthemorrhagic hydrocephalus (PHH), which requires shunt surgery in up to 70% of cases.3 IVH is associated with brain damage, especially to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
219
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(236 citation statements)
references
References 41 publications
7
219
1
6
Order By: Relevance
“…We previously demonstrated that local intraventricular transplantation of 1 × 10 5 MSCs significantly attenuated brain injury and the progress of PHH after severe IVH in newborn rats 21. With systemic intravenous administration, doses fivefold higher were required for equivalent therapeutic efficacy 15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that local intraventricular transplantation of 1 × 10 5 MSCs significantly attenuated brain injury and the progress of PHH after severe IVH in newborn rats 21. With systemic intravenous administration, doses fivefold higher were required for equivalent therapeutic efficacy 15.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to adult tissue‐derived MSCs, its advantages include easier extraction, lower immunogenicity 16, higher in vitro proliferation capacity 17, 18, and better in vivo therapeutic efficacy 19. Recently, we have shown that xenotransplantation of human UCB‐derived MSCs significantly attenuates brain injury and the progress of PHH after severe IVH in immunocompetent newborn rats 15, 20, 21. Furthermore, we have observed that treatment of BPD in premature infants with intratracheal transplantation of allogeneic human UCB‐derived MSCs is safe, feasible, and not associated with adverse respiratory, growth, or neurodevelopmental effects 22.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their multilineage differentiation potential, the protective effects of MSC transplantation were initially ascribed to the engraftment of these cells in injured tissues and their subsequent transdifferentiation to repair and replace damaged cells (37,38). However, the very low rate of in vivo engraftment and differentiation of transplanted MSCs (8,15,39) suggests that long-term survival of MSCs might not be essential for their beneficial effects (28,40). Therefore, the therapeutic effects of MSC transplantation might not be associated with their differentiation and direct replenishment of damaged tissue parenchymal cells.…”
Section: Pleiotropic Protective Effects Of Stem Cell Therapiesmentioning
confidence: 99%
“…Recently, several preclinical studies have demonstrated the promise of stem cell therapies in attenuating tissue injuries in newborn animal models of BPD (5-10), HIE (11), and IVH (12)(13)(14)(15). Furthermore, phase I clinical studies in newborn infants with BPD (16), HIE (17), or severe IVH have shown that stem cell treatments for newborn infants might be safe, feasible, and potentially efficacious.…”
mentioning
confidence: 99%
“…The rotarod test was conducted to evaluate the motor function of rats as described by Ahn et al 14 All the animals were trained for the test 1 day before surgery. Only rats with a latency of >60 s before falling off were used for analysis.…”
Section: Functional Behavioral Testmentioning
confidence: 99%